Educação emocional na abordagem ao baixo rendimento escolar na educação básica: um olhar a partir da concepção da educação popular - Soares, Lupercia Jeane (2022)
This research sought to understand the emotions of the students who have low school performance. Therefore, theoretical perspectives and pedagogical practices were analyzed to address the emotional issues that permeate low school performance during the schooling process of basic education in the early years of elementary school. The research sought to identify significant aspects of the relationship between emotion and learning; which emotions were manifested in students who have unsatisfactory performance; situate the concepts of Popular Education and Emotional Education from a theoretical and pedagogical point of view; problematize the challenges of Popular Education and Emotional Education as pedagogical strategies to approach low school performance in the context of public schools. This study has a qualitative nature, based on the perspective of Hermeneutic Phenomenology in the field of Popular Education. The empirical data were produced at the Escola Municipal de Educação Infantil e Ensino Fundamental em Tempo Integral Augusto dos Anjos (Early Childhood Education and Elementary School), located in the city of João Pessoa; through semi- structured interviews with Basic Education educators who observe the phenomenon of low school performance in their students. Data analysis was based on phenomenology, in which data were synthesized into units of meaning and systematized into analysis categories according to the research objectives. Studies on popular education such as Paulo Freire, Carlos Rodrigues Brandão, Danilo Streck, Eduardo Wanderley were taken as a theoretical reference; on low school performance and social issues: Miguel Arroyo, Bernard Charlot, Álvaro Marchesi and Eva Maria Pérez; regarding emotional issues, concepts of emotions and their characteristics: António Damásio, José Maria Martins, Rafael Bisquerra, Juan Casassus, Elisa Gonsalves; on learning processes and motivations for learning: Humberto Maturana, Francisco Varela, Alexei Leontiev. In the construction of the thesis, the intertwined paths of the researcher and her experience in basic education were studied and problematized, including aspects of her personal life trajectory until her performance as a researcher of educational practice. The relationships between popular education, emotional education and approaches to low school performance were analyzed in the critical reflection on the interfaces between emotion, learning and low school performance, emphasizing especially the significants aspects of the relationship between emotion and learning. Also noteworthy was the dimension of the family-school relationship and its impact on low school performance; the student’s behaviors as emotional indicators in the context of the classroom; the emotions that were manifested in students with low school performance in a school of popular context. The research findings indicate that the emotions of students who have low school performance can limit their ability to overcome, so it is essential to understand such emotions to build emotional regulation strategies to recognize their capabilities to face low school performance and child empowerment through the theoretical perspectives of popular education and emotional education, building an education that recognizes basic education students as subjects with rights. Aspects of limits and fragility in the knowledge and appropriation of emotional education by teachers in the school context were identified, as well as the challenges of liberating popular education in coping with low school performance and the possibilities of popular education and emotional education as pedagogical strategies to address this issue.The dialogue between popular education and emotional education enables the development of what we characterize as liberating emotional popular education, based on the right to learn and on strengthening the human person as critical and autonomous.